Gender and the total work of older workers in Asia - Gretchen Donehower (Asian Development Bank (ADB), 2023)
In Asia, aging countries with slow population growth worry about a lack of workers in the future and see older people's labor as a potential solution. However, this leaves out the work that many older people already do-unpaid care work. Drawing on data from Bangladesh, India, Mongolia, and Thailand, the estimates in this paper show that older people, especially older women, are doing a great deal of work caring for others. In this case, policies that aim to increase overall market labor force effort by increasing the market labor of older people may underachieve their goals if they do not account for the older people's unpaid care work responsibilities. Finally, we use the estimates of the older people's unpaid care work to think about investments in the paid care economy that might be needed to replace unpaid care work of the older people if they increase labor market effort but not total work. These simple calculations indicate that the scale of investment required is manageable.1
Keywords: J13; J14; J22; 330; older workers; unpaid care work; care economy; labor supply